Analisis Butir Politomus dengan Model GPCM pada Pengembangan Penilaian Kinerja Keterampilan Proses Sains Mata Pelajaran Biologi - Ulfah, Aulia Hermawati; Supahar (Universitas Negeri Jakarta, 2025)
Assessment of science process skills can be conducted through tests or non-tests. However, observations, as one non-test technique, often face challenges related to space, time, and evaluator resources. A polytomous-type paper-and-pencil test was developed to address these issues. Item characteristic analysis is an essential aspect of instrument development; thus, this study reports the instrument analysis within the development of this assessment, using the item response theory approach. A total of 415 high school students in Sumedang completed 30 items depeloved. They came from four high schools selected based on the 2022 Asessmen Kompetensi Minimum (AKM) criteria. The test of 30 items had previously undergone successful content validity, construct validity, and reliability tests. Based on the item response theory assumptions, all items were eligible for analysis using this approach. Item fit testing revealed that the instrument suited the Generalized Partial Credit Model (GPCM). The analysis was performed using the R Program application. Results showed that all items (100%) were medium difficulty; 21 items (70%) had good discrimination and items (30%) exhibited high discrimination. 14 items were suggested for category reduction due to minimal delta differences or exceedingly low delta values. These findings emphasize item analysis to achieve high-quality instruments.